Outcomes of curative-intent radiotherapy in non-small cell lung cancer (NSCLC) patients with chronic obstructive pulmonary disease (COPD) and interstitial lung disease (ILD). (July 2021) - Tang, Celion; Mistry, Hitesh; Bayman, Neil; Chan, Clara; Cobben, David; Faivre-Finn, Corinne; Harris, Margaret; Kennedy, Jason; Pemberton, Laura; Price, Gareth; Sheikh, Hamid; Woolf, David; et al.
Highlights: FEV1 (as a continuous variable) and COPD severity do not predict worse survival after NSCLC radiotherapy. Low FEV1 should not contraindicate curative-intent NSCLC radiotherapy. Patients with ILD had poor survival/high 90-day mortality after NSCLC radiotherapy. Risk/benefit assessment should inform NSCLC radiotherapy decisions in ILD patients. COPD/ILD patients were more breathless/needed more oxygen after NSCLC radiotherapy. Abstract: Outcomes of non-small cell lung cancer (NSCLC) patients with chronic obstructive pulmonary disease (COPD n  = 587) and interstitial lung disease (ILD n  = 34) treated with curative-intent radiotherapy were retrospectively investigated. Presence of ILD but not decreased forced expiratory volume in 1-second correlated with poor overall survival. Increased breathlessness and oxygen requirements after radiotherapy were observed in severe/very severe COPD and ILD.